Perspective on Blockchain Adoption Readiness at PT Soko Rindam Utama - Ramadhan, Muhammad Justio; Hendayani, Ratih (Jurnal Locus Penelitian dan Pengabdian, 2025)
Blockchain and smart contract technologies are recent digital innovations that offer advantages in terms of security, efficiency, and transaction effectiveness by eliminating the need for third-party intermediaries through automation mechanisms. The adoption of these technologies requires an in-depth analysis of various factors influencing organizational readiness. This study aims to analyze the readiness model for blockchain adoption at PT Soko Rindam Utama by examining variables such as trialability, security, complexity, innovativeness, cost, facilitating conditions, market dynamics, regulatory support, and partner readiness. A quantitative research method was employed, with data collected through questionnaires distributed to all 35 respondents using a saturated sampling technique. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings are expected to provide a comprehensive understanding of the key factors influencing blockchain adoption readiness within the organization and to serve as a basis for future strategic decision-making.